An Analytical Study -Mergers and Acquisition of Banks in India (International Journal of Scientific Research and Management (IJSRM), 2015)
Mergers and acquisitions become the key force at intervals the changing surroundings. The policy of relaxation, liberalize and globalization of the economy has exposed the corporate sector to domestic and world competition. It’s true that there is little or no scope for firms to be told from their past experience. Therefore, to figure out the success of a merger, it’s to be discovered if there is gain from mergers. it is vital to visualize the liquidity performance of those banks to visualize whether or not or not those banks have adequate assets to satisfy its current obligations. This study is restricted to a sample of banks that underwent merger. it’s projected to visualize the liquidity performance of the seven sample acquirer and target corporations before and once the quantity of mergers The study found that the banks augmented their performance once the merger event